1991
DOI: 10.1007/bf00007444
|View full text |Cite
|
Sign up to set email alerts
|

Patterns, trends, and rates of evolution within the Actinistia

Abstract: The interrelationships of 31 actinistian species (including Latimeria chalumnae) are analyzed based on a cladistic analysis of 75 osteological characters. Inference of evolutionary trends (e.g., modification of body shape and skull morphology) from the phylogenetic patterns demonstrates that the morphology of actinistians is less conservative than has been proposed previously. This empirical cladistic approach supports two distinct tempos of evolution during an evolutionary history of 380 million years. Along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 39 publications
0
44
1
Order By: Relevance
“…(b) Morphometric methodology We have used relative warps analysis (Bookstein 1991) to summarize variation in coelacanth body form, unlike previous studies, which have examined discrete character data (Schaeffer 1952;Cloutier 1991b;Smith 1994;Forey 1998). Eleven landmarks were digitized from published reconstructions or specimen photographs of 22 genera using the program tpsDig v. 1.40 (Rohlf 2004a).…”
Section: Methodsmentioning
confidence: 99%
“…(b) Morphometric methodology We have used relative warps analysis (Bookstein 1991) to summarize variation in coelacanth body form, unlike previous studies, which have examined discrete character data (Schaeffer 1952;Cloutier 1991b;Smith 1994;Forey 1998). Eleven landmarks were digitized from published reconstructions or specimen photographs of 22 genera using the program tpsDig v. 1.40 (Rohlf 2004a).…”
Section: Methodsmentioning
confidence: 99%
“…However, early in their evolutionary history, they exhibit a wide array of caudal fin forms, from tapering to heterocercal (Schultze, 1973;Forey, 1998;Long, 1999;Friedman and Coates, 2006). After the Mississippian, they are believed to have been morphologically static (Schaeffer, 1948(Schaeffer, , 1952MoyThomas and Miles, 1971;Lund and Lund, 1985;Schultze, 1987;Cloutier, 1991;Schultze, 2004), adhering closely to a body plan comparable to that of the extant coelacanth Latimeria Smith, 1939. A number of authors have suggested that peak species diversity of coelacanths occurred in the Early Triassic (Schaeffer, 1948(Schaeffer, , 1952Forey, 1984Forey, , 1988Cloutier, 1991;Cloutier and Forey, 1991;Forey, 1991Forey, , 1998; however, there is disagreement over the implications of this peak.…”
Section: Introductionmentioning
confidence: 96%
“…Coelacanths are traditionally thought of as an evolutionarily conservative group of sarcopterygian fishes that have changed little over geological time (Huxley, 1861(Huxley, , 1935Schaeffer, 1948Schaeffer, , 1952Moy-Thomas and Miles, 1971;Jarvik, 1980;Forey, 1984;Lund and Lund, 1985;Schultze, 1987;Balon et al, 1988Cloutier, 1991Schultze, 2004). However, early in their evolutionary history, they exhibit a wide array of caudal fin forms, from tapering to heterocercal (Schultze, 1973;Forey, 1998;Long, 1999;Friedman and Coates, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…Because of their significant evolutionary status, some of the Miguasha fish species have been systematically included in the majority of phylogenetic analyses published over the past 20 years: Euphanerops in lower vertebrate phylogenies (Donoghue et al 2000;Gess et al 2006;Sansom et al 2010); Triazeugacanthus and Homalacanthus in basal gnathostome phylogenies (Brazeau 2009;Davis et al 2012); Cheirolepis in actinopterygian and osteichthyan phylogenies (Cloutier and Arratia 2004); Miguashaia in actinistian, sarcopterygian and osteichthyan phylogenies (Cloutier 1991b;Forey 1998;Zhu et al 2009); Scaumenacia in dipnoan phylogenies (Lloyd et al 2012); Eusthenopteron in osteolepiform, sarcopterygian, and early tetrapod phylogenies (Cloutier and Ahlberg 1996;Ahlberg and Johanson 1998); and Elpistostege in early tetrapod phylogenies (Daeschler et al 2006;Ahlberg et al 2008). (Fig.…”
Section: Evolutionary Significance Of the Miguasha Biotamentioning
confidence: 99%